2019
DOI: 10.1016/j.pmedr.2019.100880
|View full text |Cite
|
Sign up to set email alerts
|

The development of child and adult care food program best-practice menu and training for Native American head start programs: The FRESH study

Abstract: New Child and Adult Care Food Program (CACFP) meal patterns and best practices were implemented nationally in 2017 to address the shift in dietary need from ensuring essential nutrient consumption to chronic disease prevention. Young American Indian (AI) children have disproportionately higher risk of chronic disease. Some AI tribes operate early care and education (ECE) programs and have the opportunity to participate in the CACFP. The purpose of this paper is to describe a CACFP best-practice menu and traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…The last component included menu modifications at the ECE programs. Further description of the menu modifications from the FRESH study can be found elsewhere [26][27][28]. In short, fresh vegetables from Osage Nation's Harvest Land farm were harvested and delivered to the ECEs to be incorporated into the ECE menus.…”
Section: Menu Modificationsmentioning
confidence: 99%
“…The last component included menu modifications at the ECE programs. Further description of the menu modifications from the FRESH study can be found elsewhere [26][27][28]. In short, fresh vegetables from Osage Nation's Harvest Land farm were harvested and delivered to the ECEs to be incorporated into the ECE menus.…”
Section: Menu Modificationsmentioning
confidence: 99%
“…A menu was developed for all of the ECE programs moving the community toward best practices identified by the Child and Adult Care Food Program (CACFP) ( 50 ) and has been described in detail elsewhere ( 51 ). In short, menus were designed to add fruits and vegetables as snacks, replace refined grains with whole grains, serve lean meats, nuts, and legumes, reduce fried foods, and eliminate sugary beverages and juices.…”
Section: Methodsmentioning
confidence: 99%
“…The menu changes were determined based on the amounts of produce Bird Creek Farm could grow and deliver regularly and the ECE staffing and space needs. Once the menu was finalized the teachers and cooks participated in a three-hour interactive training session to introduce the menu modifications ( 51 ), discuss the importance of the CACFP best practices, and address any challenges raised during the interactive session.…”
Section: Methodsmentioning
confidence: 99%
“…The FRESH study used a communitybased participatory research process that involved Osage Nation tribal leaders from the early childhood education and agricultural sectors in every aspect of the research, from the development of the research questions and study implementation to the data collection, analysis, and dissemination of the findings. As 1 element of a multicomponent intervention for ECE families, the FRESH preschool curriculum was accompanied by a school menu best practices redesign 16 and a supplemental teacher training on responsive feeding practices 17 described elsewhere. Intervention ECE school menus incorporated local, fresh, and culturally tailored foods from the tribe's newly launched farm.…”
Section: Food Resource Equity and Sustainability For Health Study Overviewmentioning
confidence: 99%